The role of representative design in talent development: a comment on "Talent identification and promotion programmes of Olympic athletes" - Pinder, R. A.; Renshaw, I.; Davids, K. (Journal of Sports Sciences, 2013)
In this "Letter to the editor" the authors comment the role of representative design in talent development as a comment on "Talent identification and promotion programmes of Olympic athletes". In their conclusion, a key challenge for sport scientists interested in talent identification is to consider environmental constraints and accurately predict the performance environment of the future. Such an advance in methodology may prevent talented individuals from being de-selected from programmes.